Universal geometric frustration in pyrochlores - B. A. Trump (Nature Portfolio, 2018)
The family of pyrochlore complex oxides includes many materials of fundamental or practical interest, such as spin ices and dielectrics. Trump et al. show that flexibility of the pyrochlores’ structure leads to local displacements that explain some of their unusual physical properties.